Medication Adherence and Its Influencing Factors in Postoperative Thyroid Cancer Patients: A Cross-Sectional Study - Wen Li; Luxin Yu; Hui Zheng; Kim Geok Soh; Kim Lam Soh (Nursing Research and Practice)
Conclusion: Improving patients’ self-efficacy in rational medication and strengthening patients’ health education are important ways to enhance patients’ medication adherence.